Penggunaan Extrafine Beclometason Diproprionat/Formoterol Fumarat pada PPOK : [Combined Extrafine Beclomethason Diproprionat/Formoteral Fumarat in COPD] - Sakinatus Syarifah; Muhammad Amin (Jurnal Respirasi, 2019)
Chronic obstructive pulmonary disease (COPD) is a condition characterised by poorly reversible airflow limitation that is generally progressive and causes serious disability. Exacerbations and co-morbidities contribute to the overall severity in individual patients. A fixed-dose inhaled corticosteroid/long-acting β2-agonist (ICS/LABA) combination of extrafine beclometasone dipropionate and formoterol fumarate (BDP/FF) has been recently approved for use in COPD. Small airway inflammation and remodelling are cardinal features of COPD; therefore, the ability of this extrafine formulation to reach the small, as well as the large, airways is likely to be therapeutically important by enabling treatment of inflammatory processes in the whole bronchial tree. The clinical development of extrafine BDP/FF has demonstrated significant benefits over extrafine FF in terms of lung function improvement and reduction of the exacerbation rate, thus supporting the beneficial effect of an ICS combined to a LABA in COPD patients. Head-to-head comparison studies versus other ICS/LABA combinations have shown that extrafine formulation enables clinical benefits to be achieved with a lower dose of ICS. Extrafine BDP/FF showed lung function and dyspneea improvements comparable to other ICS/LABAs, and a significantly faster onset of action was observed when compared with a salmeterol-containing fixed-dose combination.